(untitled) (Papeles, 2021)
Introduction: The present study, which deals with teaching strategies as a motivational tool, discusses the impact of gamification and interest in the contents of Physical Education, in the educational curriculum and its impact on the motor development of the learning subjects and the affective area. The research question is: How does gamification in Physical Education influence motivation in the academic process of students in the Dominican Republic? The main purpose was to analyze gamification in the Physical Education class as a didactic strategy for academic motivation in the Dominican Republic. Methodology: As support, it was based on the desk research methodology, which consists of the study and analysis of educational methods and practices that are used in each of the educational levels, with preeminence in the secondary level. In this sense, an organized and systematized review of studies that address the motivational issue in educational institutions and its impact on contemporary pedagogy was conducted. The databases consulted were: Scopus, SciELO and Google Scholar, a total of 20 references. Results and discussion: The results show that the gamification of Physical Education at the Secondary Level of Dominican education is important to motivate their study and learning in a significant way, which substantially improves academic performance in their integral formation. Conclusions: In conclusion, theories, documents and authors consider it as a primary factor in the motivation of students and in the case of Physical Education.